Hubungan Minat Belajar dan Asal Jurusan terhadap Prestasi Belajar Mahasiswa Program Studi Teknik Informatika STIKOM Tunas Bangsa Pematangsiantar - Fitri Anggraini; Ika Okta Kirana; Zulaini Masruro Nasution (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This research is a qualitative descriptive study which aims to determine the relationship between interest in learning and origin of major on the learning achievement of students in the STIKOM Tunas Bangsa Pematangsiantar Informatics Engineering Study Program. Interest in learning is one of the internal factors that influences learning achievement, while the origin of the major is the major that the student has taken while in high school. There are a total of 61 students from the STIKOM Tunas Bangsa Informatics Engineering Study Program in the Class of 2023 using purposive sampling because the Class of 2023 are still classified as new students and already have a Grade Point Average (GPA). The instruments used are observations and questionnaires, which have been tested for validity and reliability. The data was analyzed using a multiple linear regression analysis model. The results of the research show that there is no significant simultaneous influence between interest in learning and origin of major on the learning achievement of students in the Information Engineering Study Program at STIKOM Tunas Bangsa Pematangsiantar with a significance value of 0.007.